2007
DOI: 10.1897/06-523r.1
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of copper, ammonia, and chlorine to glochidia and juveniles of freshwater mussels (unionidae)

Abstract: The objective of the present study was to determine acute toxicity of copper, ammonia, or chlorine to larval (glochidia) and juvenile mussels using the recently published American Society for Testing and Materials (ASTM) Standard guide for conducting laboratory toxicity tests with freshwater mussels. Toxicity tests were conducted with glochidia (24- to 48-h exposures) and juveniles (96-h exposures) of up to 11 mussel species in reconstituted ASTM hard water using copper, ammonia, or chlorine as a toxicant. Cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
153
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(181 citation statements)
references
References 23 publications
20
153
5
Order By: Relevance
“…Even after the improvement of Lake Orta conditions and the neutralization of pH values accomplished by liming (1989)(1990), studies documenting the progressive recovery of both pelagic and benthic populations (Baudo et al, 2001a;Bielli and Tesauro, 2001;Nocentini et al, 2001) failed to reveal the presence of mussels or any other molluscs. Since mussels are highly sensitive to acidification (Økland and Økland, 1986;Taskinen et al, 2011), ammonia (Augspurger et al, 2003;Wang et al, 2008) and heavy metals (Naimo, 1995;Keller et al, 2006), particularly at the earlier life stages (Wang et al, 2007a(Wang et al, , 2007bCope et al, 2008;Cleawater et al, 2014), the high sediment toxicity, that did not improved but was rather worsened by liming, likely hindered recolonization. Furthermore, once extirpated from a water body, mussels are not able to recolonize easily, particularly if they lack access to restocking populations (Strayer et al, 2004), due to constraints related to their complex life cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even after the improvement of Lake Orta conditions and the neutralization of pH values accomplished by liming (1989)(1990), studies documenting the progressive recovery of both pelagic and benthic populations (Baudo et al, 2001a;Bielli and Tesauro, 2001;Nocentini et al, 2001) failed to reveal the presence of mussels or any other molluscs. Since mussels are highly sensitive to acidification (Økland and Økland, 1986;Taskinen et al, 2011), ammonia (Augspurger et al, 2003;Wang et al, 2008) and heavy metals (Naimo, 1995;Keller et al, 2006), particularly at the earlier life stages (Wang et al, 2007a(Wang et al, , 2007bCope et al, 2008;Cleawater et al, 2014), the high sediment toxicity, that did not improved but was rather worsened by liming, likely hindered recolonization. Furthermore, once extirpated from a water body, mussels are not able to recolonize easily, particularly if they lack access to restocking populations (Strayer et al, 2004), due to constraints related to their complex life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…No data is available on sediment chemistry after 1996 ) when the area colonized was highly enriched in Cu (~2000 mg kg -1 ), Cr (~1000 mg kg -1 ), Pb (~500 mg kg -1 ) and Mn (~1500 mg kg -1 ) with pore water concentrations of Cu and Cr respectively of 0.63 and 0.10 (Guilizzoni et al 2001) the layer deposited between 1996 and 2001 (about 1 cm) was probably not sufficient to isolate organisms from the toxic layers underneath. Furthermore, juvenile mussels, which have higher sensitivity to toxicants than adults (Wang et al, 2007a(Wang et al, , 2007b regularly burrow deeper than 5 cm and even as deep as 20 cm (<3-cm size class; Schwalb and Pusch, 2007) becoming more exposed than adults to sediment bound contaminants (Yeager et al 1994). We must therefore conclude that Unio elongatulus was able to recolonize, although the sediments were still contaminated by metals with concentrations largely exceeding the level known to have acute and chronic effects on most freshwater mussel species (Wang et al, 2007a(Wang et al, , 2007bUS-EPA, 2007;Clearwater et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ammonia levels in springs are typically lower than U.S. Environmental Protection Agency Aquatic Life Ambient Water Quality Criteria, but ammonia is usually present in most groundwater wells and springs tested Katz et al 2009;EPA 2013). Ammonia is extremely toxic to larval and juvenile freshwater mussels (Wang et al 2007), and may persist longer in springs than in other systems because of low dissolved oxygen and eutrophic conditions limiting bacterial nitrification (Haag 2012). In areas where spring water has limited opportunity to mix with atmospheric oxygen (e.g., short spring runs, midchannel springs), the potential exists for ammonia to reach levels toxic to juvenile freshwater mussels.…”
Section: Other Watershed Variablesmentioning
confidence: 99%
“…Although the acute Cu sensitivity of glochidia has been assessed in a variety of mussel species [8,10,11], the diversity of the exposure water used in those studies was very limited. Typically, reconstituted waters have been used to determine an organism's sensitivity to a contaminant and, although such standardized waters are useful for comparing sensitivities among species and among studies, they do not necessarily reflect the complexity of the water found in an organism's natural habitat.…”
Section: Effect Of Doc On Cu Toxicity To Glochidiamentioning
confidence: 99%